Optimization of the Application of Work Discipline in Improving the Performance of Movement Control Apron Officers at Adi Soemarmo International Airport - Sherly Oktavia Putri; Kifni Yudianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The Apron Movement Control (AMC) Unit has responsibility as executor of duties in supervision, service, and security in the Apron area. therefore officers are expected to be able to carry out their duties and responsibilities optimally. The purpose of this study was to determine the optimization of the application of work discipline in improving the performance of Apron Movement Control (AMC) officers at Adi Soemarmo Boyolali International Airport. This study uses descriptive qualitative research methods, data collection is done by structured interviews, participatory observation and documentation. Structured interviews were conducted with three informants, two of whom were airline service supervisors and one Apron Movement Control (AMC) officer on duty at Adi Soemarmo Boyolali International Airport. The data analysis technique uses the theory from Miles and Huberman. The validity of the data uses source triangulation, technical triangulation and reference materials. The results of the study show that the application of work discipline carried out at the Apron Movement Control (AMC) unit at Adi Soemarmo Boyolali airport has been running quite optimally and optimally, but indeed in practice there are still found officers who do not comply with company regulations, maybe for the next supervisors and leaders can be more assertive in paying attention to work discipline and performance in the Apron Movement Control (AMC) unit directly in the field. While maintaining work discipline is something that needs attention, don't let supervisors and leaders be careless because everything is going well, implementing continuous work discipline is the best step in achieving more optimal performance.